Assessment of lesion-induced network connectivity disruption in the human brain: application to a context of pre-surgical planning - Henriques, Laeticia (2020)
Tese de mestrado integrado, Engenharia Biomédica e Biofísica (Engenharia Clínica e Instrumentação Médica) Universidade de Lisboa, Faculdade de Ciências, 2020